WRITTEN ON THE BORDER: YOLANDA GARCÍA’S HYPHENIZATION IN JULIA ALVAREZ’S “ANTOJOS” - Matias-Ferreira, Jr., Tito (Caderno Seminal, 2019)
This article aims at discussing the fictional representation of Caribbean immigrants in the novel How The García Girls Lost Their Accents (1991), by Julia Alvarez. The mediations among the condition of the immigrant, his/her relationship with the border, with his/her exile and mainly with the subject of the hegemonic culture of the country they live in are what it takes to apprehend the process of the position of contemporary diasporic subjects. The implications of such negotiations in the lives of immigrants are relevant issues in the writing of Julia Alvarez, as well as other contemporary writers. When describing the immigration of the García sisters to the United States, Julia Alvarez in her novel How the Garcia Girls Lost Their Accents depicts the way the Garcías constantly tout between their Caribbean and US portions both in the Caribbean as well as in the US. Thus, the purpose of this article is to understand the changes experienced by Alvarez’s characters after they are forced to immigrate to the United States and strive to reconcile their identity(ies) marked by border(s). Also, this discussion will be especially based on the impact of immigration on Alvarez’s diasporic subjects and the development of their hyphenated identity in the U.S. For this, the paper will also consider the language issue for the construction of the immigrant identity insofar as bilingualism is a key factor in the negotiation the García girls must effect between their Caribbean and their American halves in order to understand where they stand.